2006
DOI: 10.1111/j.1439-0485.2006.00102.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes of soft‐bottom zoobenthic communities in and around Alsancak Harbor (Izmir Bay, Aegean Sea), with special attention to the autecology of exotic species

Abstract: Temporal and spatial variation in soft‐bottom benthic communities following recovery from a pollution episode were studied between January and September 2004 in and around Alsancak Harbor, located in the polluted part of Izmir Bay (Aegean Sea, eastern Mediterranean). Samples were collected at seven stations by van Veen grab. Three additional stations were sampled by means of a beam trawl to take into account large mobile animals and for a better estimate of the local biodiversity. A total of 231 species belong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 26 publications
3
41
1
2
Order By: Relevance
“…Körfezin iç kesimlerinde kirlilik aşırı boyutlara ulaşmış ve körfezin ekolojik dengesinde onarılması güç bozulmalar gözlenmeye başlanmıştır. Bu nedenlerden dolayı 1983 yılında Büyük Kanal Projesi çerçevesinde arıtma tesisi kurma çalışmaları başlatılmış, bu tesisinin büyük bir kısmının 2000 yılında devreye girmesi ile orta ve iç körfezde fiziksel, kimyasal ve biyolojik değişiklikler söz konusu olmaya başlamıştır (Kontaş et al, 2004;Çınar et al, 2006). İzmir iç körfezde yer alan İzmir Limanı'ndan kaynaklanan yoğun gemi trafiğinin de körfez ekosistemi üzerinde olumsuz etkileri vardır.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Körfezin iç kesimlerinde kirlilik aşırı boyutlara ulaşmış ve körfezin ekolojik dengesinde onarılması güç bozulmalar gözlenmeye başlanmıştır. Bu nedenlerden dolayı 1983 yılında Büyük Kanal Projesi çerçevesinde arıtma tesisi kurma çalışmaları başlatılmış, bu tesisinin büyük bir kısmının 2000 yılında devreye girmesi ile orta ve iç körfezde fiziksel, kimyasal ve biyolojik değişiklikler söz konusu olmaya başlamıştır (Kontaş et al, 2004;Çınar et al, 2006). İzmir iç körfezde yer alan İzmir Limanı'ndan kaynaklanan yoğun gemi trafiğinin de körfez ekosistemi üzerinde olumsuz etkileri vardır.…”
Section: Introductionunclassified
“…İzmir Körfezi'nde daha önce gerçekleştirilen çalışmalarda (Demir, 1977;Öztürk and Poutiers, 2005;Çınar et al, 2006;2008;Doğan et al, 2014) özellikle yumuşak substratumlardan tespit edilen yabancı bivalv türlerine değinilmiş olup günümüze kadar, yabancı bivalv türlerinin sert substratumlarda yer alan midye fasieslerindeki kalitatif ve kantitatif durumlarına ilişkin bir çalışma gerçekleştirilmemiştir. İzmir Körfezi medio-littoral zon midye fasieslerinde dağılım gösteren ve özellikle körfezde istilacı olma potansiyeline sahip yabancı bivalv türlerinin mevcut durumlarının tespiti bu çalışmanın konusunu teşkil etmektedir.…”
Section: Introductionunclassified
“…Amphibalanus amphitrite (Darwin 1854) Şen et al, 2010Neu, 1939Neu, 1939Pınar, 1974 Amphibalanus eburneus (Gould 1841) Pınar, 1974Ostroumoff, 1894Pınar, 1974Pınar, 1974 Tylos europaeus Arcangeli, 1938 A terrestrial species that can be found in supralittoral Geldiay and Kocataş, 1972a;Bakır and Çevirgen, 2010 Tylos latreillei Audouin, 1826 A terrestrial species that can be found in the supralittoral Geldiay and Kocataş, 1972b;Geldiay et al, 1977;Kocataş and Katağan, 1983;Kırkım et al, 2005;Kırkım et al, 2006 AMPHIPODA Amphilochoides longimanus (Chevreux, 1888) Suspicious, no record from Mediterranean Sea, confirmation needed Kocataş and Katağan, 1978 Byblis gaimardii (Krøyer, 1846) Suspicious, no record from Mediterranean Sea, confirmation needed Ostroumoff, 1894…”
Section: Sessilia (Order)mentioning
confidence: 99%
“…Other species in the genus (e.g. H. dianthus, H. sanctaecruci, H. ezoensis) are also common foulers (Ç inar et al 2006;Lewis et al 2006). Historically the interest in the fouling characteristics of these poly chaetes and other organisms was linked to their effects on fuel consumption due to an increase in drag on ships, the damage done to the surface of ships and marine piping networks, all of which increase economic costs.…”
Section: Introductionmentioning
confidence: 99%